Effective Risk Management Strategies for Small and Medium-Sized Enterprises (SMEs) to Mitigate Interest Rate Fluctuation Risks and Ensure Financial Sustainability - Hadiat, Aisha Nurul Qolbi; Anjani, Niken Pinkyvita Nur (Rescollacom (Research Collaborations Community), 2024)
This research aims to delve into the multifaceted challenges that Small and Medium-sized Enterprises (SMEs) encounter in the wake of interest rate fluctuations and proposes effective risk management strategies. Through an extensive review of existing literature, case studies, this paper not only explores the impact of interest rate volatility on SMEs but also provides strategies to enhance their financial resilience